دور الإدارة الإلكترونية في تفعيل عملية التخطيط: دراسة ميدانية لمؤسسة كوندور برج بوعريريج الجزائر - رحماني, سناء; رحماني, موسى (جامعة الوادي University of Eloued, 2016)
تهدف هذه الدراسة إلى إبراز الدور الذي تلعبه الإدارة الإلكترونية في تفعيل عملية التخطيط، ومدى تطبيق مؤسسة كوندور للإدارة الإلكترونية، وقد تكوّن مجتمع الدراسة من 152 إداري، وبلغت العينة 79 إداري أخذت بطريقة عشوائية. وتم توزيع استمارة استبيان تحتوي على ثلاث أقسام، خصص القسم الأول لرصد البيانات الشخصية والوظيفية لأفراد العينة، بينما القسم الثاني فخصص لعناصر الإدارة الإلكترونية وتضمن 28 عبارة، بينما القسم الثالث فخصص لعملية التخطيط وتضمن 11 عبارة. وأظهرت نتائج الدراسة أنّ تطبيق مؤسسة كوندور للإدارة الإلكترونية يرقى إلى المستوى المطلوب، فهي تتوفر على عناصر الإدارة الإلكترونية، وفي مقدمتها العنصر البشري، تليه أجهزة الحاسوب وملحقاته، ثم قواعد البيانات والبرمجيات، وفي الأخير شبكات الاتصال، كما أن الإدارة الإلكترونية بكل عناصرها ساهمت في تفعيل عملية التخطيط بمؤسسة كوندور. The conducted study aims primarily to highlight the significant role carried by an electronic management, in planning effectively, as well as to measure the extent to which this method is being applied by Condor Electronics. The aforementioned study included a population of 152 administrators, out of which a sample of 79 was taken at random. The devised questionnaire can be divided into three sections. The first of which targeted mainly social and professional background information. Whereas the second included up to 28 sub-sections seeking e-management related data. As for the third section, the focus shifted toward the planning process dedicating 11 sub-sections. Eventually, the findings of this study has demonstrated that Condor Electronics has indeed succeeded in implementing e-management commendably by adequately providing all necessary e-management elements, ranging from personnel, to equipment such as computers, to programs and databases, to communication networks. To conclude, the attained data evidently shows how crucial e-management is in ensuring an effective planning process for Condor Electronics
The Role of E-management in the Process of Planning -A Field Study for Condor Electronics -Bordj Bou Arreridj
مقال- مجلة رؤى اقتصادية
Keywords: الإدارة الإلكترونية – التخطيط; E-management (i.e. Electronic management) – Planning